2022
DOI: 10.1007/s10340-022-01544-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of two omnivorous iolinid mites as predators of the tomato russet mite, Aculops lycopersici

Abstract: Two iolinid predatory mites were studied in the laboratory as potential biological control agents of the tomato russet mite, Aculops lycopersici (Acari: Eriophyidae). The development, reproduction and predation capacity of Pronematus ubiquitus and Homeopronematus anconai (Acari: Iolinidae) on A. lycopersici were investigated. Developmental time from egg to adult at 25°C averaged 9.59, 9.31 and 9.52 days for P. ubiquitus on A. lycopersici, A. lycopersici and Typha angustifolia pollen, and pollen only, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In the case of P. ubiquitus, this could be pollen (T. angustifolia, which was provided weekly), fungi or plant sap. [18][19][20] The population density of P. ubiquitus appeared to be independent of the pest A. lycopersici. A laboratory trial showed that survival and fecundity were similar when P. ubiquitus was fed with pollen plus A. lycopersici or pollen only.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In the case of P. ubiquitus, this could be pollen (T. angustifolia, which was provided weekly), fungi or plant sap. [18][19][20] The population density of P. ubiquitus appeared to be independent of the pest A. lycopersici. A laboratory trial showed that survival and fecundity were similar when P. ubiquitus was fed with pollen plus A. lycopersici or pollen only.…”
Section: Discussionmentioning
confidence: 96%
“…When the density of a particular prey species is low, the generalist predator will feed on something else. In the case of P. ubiquitus , this could be pollen ( T. angustifolia , which was provided weekly), fungi or plant sap 18–20 . The population density of P. ubiquitus appeared to be independent of the pest A. lycopersici .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations